CD4(+) T cell dependent IFN-γ production by CD8(+) effector T cells in M. tuberculosis infection - Bold, Tyler D. (2012)
Both CD4(+) and CD8(+) T cells contribute to immunity to tuberculosis, and both can produce the essential effector cytokine IFN-γ. However, the precise role and relative contribution of each cell type to in vivo IFN-γ production are incompletely understood. To identify and quantitate the cells that produce IFN-γ at the site of M. tuberculosis infection in mice, we used direct intracellular cytokine staining ex vivo without restimulation. We found that CD4(+) and CD8(+) cells were predominantly responsible for production of this cytokine in vivo and we observed a remarkable linear correlation between the fraction of CD4(+) cells and the fraction of CD8(+) cells producing IFN-γ in the lungs. In the absence of CD4(+) cells, a reduced fraction of CD8(+) cells were actively producing IFN-γ in vivo, suggesting that CD4(+) effector cells are continually required for optimal IFN-γ production by CD8(+) effector cells. Accordingly, when infected mice were treated intravenously with an MHC-II-restricted M. tuberculosis epitope peptide to stimulate CD4(+) cells in vivo, we observed rapid activation of both CD4(+) and CD8(+) cells in the lungs. Indirect activation of CD8(+) cells was dependent on the presence of CD4(+) cells, but independent of IFN-γ responsiveness of the CD8(+) cells. These data provide evidence that CD4(+) cell deficiency impairs IFN-γ production by CD8(+) effector cells and that ongoing crosstalk between distinct effector T cell types in the lungs may contribute to a protective immune response against M. tuberculosis. Conversely, defects in these interactions may contribute to susceptibility to TB and other infections.